Respon Beberapa Varietas Kedelai (Glycine max (L) Merril) Pada Fase Perkecambahan Terhadap Pemberian Polyethylen Glycol - Muhammad Fikkia Zhari; Syafrinal Syafrinal; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the soybean varieties which provide the best response to the germination phase with Polyethylen Glycol. This research was conducted from February to May 2019 atPlant Breeding Laboratory, Faculty of Agriculture, Riau University. The study was conducted experimentally using factorial randomized complete design with two factors, where the first factor was soybean variety: V1 (Najsmoro variety), V2 (Dena 1 variety) and V3 (Argomulyo variety). The second factor was PEG concentration: D1 (0% PEG concentration), D2 (5% PEG concentration), D3 (10% PEG concentration), D4 (15% PEG concentration), D5 (20% PEG concentration). The parameters observed were germination, Indeks value test (IVT), length of roots and plomules. The data obtained were analyzed statistically with variance and continued with a DNMRT further test at the level of 5%. The results showed that the three varieties had germination> 90% after being treated with PEG concentration. Anjasmoro and Dena 1 varieties are varieties with good germination phase after giving of PEG concentration. Keywords: Germination, Soybean varieties, Polyethylen Glycol.